Land colonization in Central America; experiences in the settlement of humid tropical lands in Panama, Costa Rica, Nicaragua, Honduras and Guatemala - Jones, J.R. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
Dat. num. 11 mapas. Bib. Sum. (En)